Desenvolvimento e validação de método multirresíduo empregando GC-MS (NCI-SIM) para determinação de pesticidas em grãos de trigo e seus produtos processados - Kolberg, Diana Inês Ströher (2008)
In this study a multiresidue method for the determination of 24 pesticides in wheat, flour, bran and bread using GC-MS (NCI-SIM) mode was developed and validated. The objective of this study was to evaluate the pesticides destination during the processing of wheat as well as during the process of milling for attainment of white flour and the bran. The degradation of these pesticides was evaluated during the bread baking process. QuEChERS method, developed originally for samples of fruits and vegetables, was modified and optimized for the extraction of different pesticides. For the extraction procedure acetonitrile containing 1% acetic acid, sodium acetate, sodium citrate and magnesium sulphate was used. The clean up using dispersive solid phase extraction was carried out with C18 and magnesium sulphate. The method was validated evaluating the following parameters: linearity (seven different levels of concentration), limit of detention (LOD), limit of quantification (LOQ), matrix effect as well as precision and accuracy, evaluating the percentage of recovery using four different spike levels. The linear range used in the analytical curves was from 1.0 to 100 μg L-1 for wheat and bread and 2.0 to 200 μg L-1 for flour and bran both with values of r2 > 0.99. Recoveries presenting values between 70 and 120% with RSD <20% were considered satisfactory for most compounds. It was observed that there was a greater concentration of pesticides in the external part of the wheat grain, and that the sample of bran presented higher concentrations than those of flour. During the baking, degradation of compounds was observed in the range of 50 to 70%. The method proved to be adequate for the multiresidue analysis of pesticides in the matrices studied and the GC-MS (NCI-SIM) technique proved to be sensitive and highly selective.